Migration Fears in the United States and the Geopolitical Risk Index - Christopher Olds (Technium Social Sciences Journal, 2020)
This study contrasts a publicly available measure of migration fears in the United States with a publicly available measure of geopolitical risk, a barometer of concern about possible disruptions to peace in international relations. The time series analyses performed on information spanning between 1990 and 2019 suggest that a change in migration fears in the U.S. increases the level of geopolitical risk, such that the U.S. appears to perceive migrants as potentially threatening and responds with an aggressive posture in interactions with other nations. The findings of the study are aligned with theories in existing academic literature about fear-induced aggression and intergroup conflict.